2018
DOI: 10.1111/ibi.12653
|View full text |Cite
|
Sign up to set email alerts
|

Trends and characteristics of imports of live CITES‐listed bird species into Japan

Abstract: Understanding the characteristics of the international bird trade is critical for preventing the traffic of endangered species. Japan is the second largest importer of birds for the pet industry globally, yet little research has examined its role in the international trade of live exotic birds. We used reports to the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Trade Database to conduct the first quantitative analysis of the live commercial bird imports to Japan. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…We did not observe any owls in Chatuchak during our visits in 2011. Nash (1993 likewise did not record any owls during any of his visits to this market.…”
Section: Owl Presence In the Brick-and-mortar Bird Marketmentioning
confidence: 48%
See 1 more Smart Citation
“…We did not observe any owls in Chatuchak during our visits in 2011. Nash (1993 likewise did not record any owls during any of his visits to this market.…”
Section: Owl Presence In the Brick-and-mortar Bird Marketmentioning
confidence: 48%
“…In Chatuchak, Chng & Eaton (2016) found that 44% of bird species and 45% of the individual birds offered for sale were not native to Thailand, and found that 97% of the turtles and tortoises on sale belonged to non-native species. Todd (2011) found 32 Malagasy species (reptiles, amphibians, mammals) offered for sale during a 1 mo survey in 2010 in Chatuchak market.…”
Section: Discussionmentioning
confidence: 99%
“…Seizure data revealed, however, that Sweden was one of the intended destinations for a shipment of live H. pustulatus. Japan, a known destination country for a variety of exotic pet species (Vall-Llosera & Su 2018;Wakao et al 2018;McMillan et al 2020), was another destination in seizure incidents, as well as Taiwan. Given that seizure data is subject to biases due to imperfect detection (Symes et al 2018), illegal trade is likely occurring at greater rates and across a greater diversity of European and Asian countries than is currently recorded.…”
Section: Discussionmentioning
confidence: 99%
“…We collated online trade data from English language and Japanese websites. Japanese websites were chosen because of anecdotal reports, it being known as a popular destination for exotic pets (Vall-Llosera & Su 2018;Wakao et al 2018;McMillan et al 2020), as well as Japan being reported as a destination in the previously recorded seizure incidents. Following the framework of Stringham et al (2020) we obtained human research ethics committee approval from the University of Adelaide (Australia) to use automated data mining and searched a total of eight international English language and eight Japanese websites, using the keywords 'sailfin' and 'Hydrosaurus', as well as in October 2020.…”
Section: © Emerson Y Symentioning
confidence: 99%
“…Critically, we provide a unique set of analyses of the drivers of the pet trade across multiple stages (from trade to escape), levels of regulation, diversity of taxa (105 families and 590 species of terrestrial vertebrates) and Australian socioeconomic metrics. Moreover, we used direct measures of pet keeping and trading quantities, rather than proxies such as market price or presence/absence records, which may suffer from key reporting biases or not accurately reflect rate of trade for all taxa (e.g., Vall-Llosera and Su (2019)). Using a Structural Equation Modelling (SEM) framework, we identified a network of interrelationships and predict the effects of pet attributes and owner demographics on trade dynamics.…”
Section: Introductionmentioning
confidence: 99%